Effects of Glucagon-Like Peptide-1 Receptor Agonists and Sodium-Glucose Cotransporter 2 Inhibitors on Intima-Media Thickness: Systematic Review and Meta-Analysis - Abolfazl Akbari; Shiva Hadizadeh; Leida Heidary (Journal of Diabetes Research)
Background. Beyond glycemic control, glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and sodium-glucose cotransporter 2 inhibitors (SGLT2is) have been proposed to reduce the risk of cardiovascular events. The aim of the present systematic review and meta-analysis is to demonstrate the effects of GLP-1 RA and SGLT2is on intima-media thickness (IMT). Methods. PubMed, EMBASE, Web of Science, SCOPUS, and Google Scholar databases were searched from inception to September 9, 2023. All interventional and observational studies that provided data on the effects of GLP-1 RAs or SGLT2is on IMT were included. Critical appraisal was performed using the Joanna Briggs Institute checklists. IMT changes (preintervention and postintervention) were pooled and meta-analyzed using a random-effects model. Subgroup analyses were based on type of medication (GLP-1 RA: liraglutide and exenatide; SGLT2i: empagliflozin, ipragliflozin, tofogliflozin, and dapagliflozin), randomized clinical trials (RCTs), and diabetic patients. Results. The literature search yielded 708 related articles after duplicates were removed. Eighteen studies examined the effects of GLP-1 RA, and eleven examined the effects of SGLT2i. GLP-1 RA and SGLT2i significantly decreased IMT (MD=−0.123, 95% CI (-0.170, -0.076), P<0.0001, I2=98% and MD=−0.048, 95% CI (-0.092, -0.004), P=0.031, I2=95%, respectively). Metaregression showed that IMT change correlated with baseline IMT, whereas it did not correlate with gender, duration of diabetes, and duration of treatment. Conclusions. Treatment with GLP-1 RA and SGLT2i can lower IMT in diabetic patients, and GLP-1 RA may be more effective than SGLT2i.